Seismic retrofit design and risk assessment of an irregular thermal power plant building. (27th January 2020) - Wang, Jianze; Dai, Kaoshan; Li, Bowei; Li, Bo; Liu, Yang; Mei, Zhu; Yin, Yexian; Li, Jiahong
Summary: Electric power system is one of essential lifeline systems for an urban community. An actual power plant building with typical coal‐fired power generation process is selected to be studied in this paper. The detrimental impacts on the seismic performance of the structural system induced by heavy coal bunkers and irregular bracing configurations are expected to be mitigated by using retrofit strategies. A total of three retrofit design schemes that employ the isolation and supplemental damping techniques are developed. The original design scheme of the actual thermal power plant building that adopts steel special concentrically braced frame as lateral‐force resisting system is used as benchmark for comparison purposes. Nonlinear response‐history analyses are performed, and the obtained seismic responses are compared. To better quantify the benefit of the considered retrofit strategies, seismic risk in terms of probabilities of exceeding designated damage states as well as the downtime are analyzed. For the studied thermal power plant building, the results show that the added damping system is more effective in seismic risk reduction than the isolation for heavy coal bunkers. Compared to the original structural system design, the use of supplemental damping system cut the downtime of the thermal power plant building at most 42%.